POLA SIDIK JARI DAN SUDUT AXIAL TRIRADIUS DIGITAL (ATD) PADA NARAPIDANA LAKI - LAKI DI TAHANAN TITIPAN (TAHTI) POLDA SUMATERA UTARA - Ismurizal Ismurizal (Jurnal Penelitian Kesmasy, 2019)
Dermatoglyphics can be used not only to identify an individual's identity but also to determine chromosomal diseases, talents, potentials, and individual personalities. Several studies were conducted to prove that dermatoglyphics have a tendency that is typical of inmates. This study aimed to find out how the ATD fingerprint and angular patterns in prisoners in the Male North Sumatra Regional Police Correctional Institution. The research sample through total sampling. The research data is in the form of fingerprint patterns and ATD angles, data collection for fingerprint patterns by attaching the fingertips of the right and left hands to the Digital person Fingerprint reader and the results are analyzed on 10 fingers. ATD angles data were obtained by applying all palmar surfaces with Blue Ink and affixed to the observation sheet to calculate the angle of ATD. Data were analyzed univariately for the type of fingerprint pattern and the angle of ATD.